Animated Videos Based on Problem-Based Learning on Social Sciences Subjects for Sixth Grade of Elementary School - Eka F. Situmorang; I Made Tegeh (Jurnal Edutech Undiksha, 2024)
There is a gap between technological advances in the world of education and teachers' ability to utilize them. Even though the shift towards digital learning is increasingly dominating, there are still many teachers who have not been able to adapt to information technology as a learning medium. This research aims to develop animation videos based on problem-based learning in social studies subjects in Class VI Elementary School. The research is included in the type of development research using the ADDIE model. The subjects involved in this research were learning content experts, learning design experts, learning media experts, 3 students for individual trials, and 9 students for small group trials. Data collection was carried out using questionnaires, interviews and field notes. Data were analyzed using qualitative data analysis methods, quantitative descriptive data analysis, and t-test. The research results show that learning animation videos with an innovative problem-based learning model for social studies have very good quality and are suitable for use in learning. The use of PBL-based learning animation videos has proven to be effective in improving students' understanding and learning achievement. It can be concluded that PBL-based learning animation videos have a positive impact in developing students' critical thinking skills and collaborative abilities. This research has implications for improving students' learning experiences, increasing engagement, and actively understanding concepts in social studies subjects.